Sex determination by three-dimensional geometric morphometrics of craniofacial form. - Chovalopoulou, Maria-Eleni; Valakos, Efstratios D.; Manolis, Sotiris K (Anthropol Anz, 2016)
SUMMARY: The purpose of the present study is to define which regions of the cranium, the upper-face, the orbits and the nasal are the most sexually dimorphic, by using three-dimensional geometric morphometric methods, and investigate the effectiveness of this method in determining sex from the shape of these regions. The study sample consisted of 176 crania of known sex (94 males, 82 females) belonging to individuals who lived in Greece during the 20(th) century. The three-dimensional co-ordinates of 31 ecto-cranial landmarks were digitized using a MicroScribe 3DX contact digitizer. Goodall's F-test was performed in order to compare statistical differences in shape between males and females. Generalized Procrustes Analysis (GPA) was used to obtain size and shape variables for statistical analysis. Shape, Size and Form analyses were carried out by logistic regression and discriminant function analysis. The results indicate that there are shape differences between the sexes in the upper-face and the orbits. The highest shape classification rate was obtained from the upper-face region. The centroid size of the caraniofacial and the orbital regions was smaller in females than males. Moreover, it was found that size is significant for sexual dimorphism in the upper-face region. As anticipated, the classification accuracy improves when both size and shape are combined. The findings presented here constitute a firm basis upon which further research can be conducted.
Keywords: Anthropology, Physical; Cephalometry; Female; Greece; Humans; Imaging, Three-Dimensional; Male; principal component analysis; Sex Determination by Skeleton; Skull